Compassion-justice conflicts and Christian ethics - Barrera, Albino (New studies in Christian ethics, 2024)
"Conflicting demands of love and justice are among the most vexing problems of social philosophy, moral theology, and public policy. They often have life-and-death consequences for millions. This book examines how and why love-justice conflicts arise to begin with and what we can do to reconcile their competing claims"--